Taxonomy of Community Response During Flood Disasters in Jakarta: A Communication Perspective - Lestari, Martha; Diniati, Anisa; Alamsyah, Purnama; Salma, Aqida Nuril (Jurnal Sosioteknologi, 2024)
Jakarta has experienced numerous significant floods since 2002, including those in 2007, 2013, and 2015, a source of concern for the residents of Jakarta. Residents of DKI Jakarta have expressed their concerns regarding the disaster on Twitter and other platforms, which offer a comprehensive account of the flood experiences of Jakarta residents, which is beneficial to stakeholders in the field of flood management. The status of an incident can be rapidly determined using Twitter data. This project investigates the Twitter responses of Jakartans to the flood disaster. The analysis of flood tweets from Jakarta residents is conducted in three phases: 2015, 2020, and 2021. Utilizing topic modeling, this initiative maps emerging topics. Topic modeling is particularly effective in the context of flood issues, as it can assist in the clustering of topics and thedissemination of specific information to the public. Seven modeling-based topic groups are used to organize twenty topics. The results of this project indicate that the majority of Jakartan flood tweets are related to "Weather Report" topics. The findings indicated that "Submerged Houses" has a substantial proportion and is anticipated to increase with each flood. The increasing number of submerged houses in Jakarta should cause concern among the local populace.